Respostas

2014-06-24T08:22:17-03:00
A expressão 2√3 + 5√12 - 3√27 é igual a:

para maior e facilidade VAMOS fazer por parte

2
√3 = 2√3
5√12   fatorar 12| 2
                      6| 2
                      3| 3
                      1/

√5√12 = 5√2.2.3  = 5√2².3 = 5.2√3 = 10√3 (elimina a √ com o (²))

3 √27   27| 3
            9| 3
            3| 3
             1/
 
 3√27 = 3√3.3.3  =  3√3².2 = 3. 3√3  = 9√3  
 
  A expressão 2√3 + 5√12 - 3√27 é igual a:
                   

2√3 + 5√12 - 3√27 =
2√3 + 10√3 - 9√3  = 
       + 12√3 - 9√3 =  3√3

  • Usuário do Brainly
2014-06-24T11:19:15-03:00
2√3 + 5√12 - 3√27
2
√3 + 5√(2 . 2 . 3) - 3√(3 . 3 . 3)
2√3 + 5√(2² . 3) - 3√(3³)
2√3 + (5 . 2)√3 - 3√(3² . 3)
2√3 + 10√3 - (3 . 3)√3
2√3 + 10√3 - 9√3
(2 + 10 - 9)√3
3√3